Augmented reality tools for mathematics and geoscience education - Rafał Kaźmierczak; Grzegorz Grunwald; Robert Skowroński; Lena Kaźmierczak; Cezary Kowalczyk (Scientific Reports)
Abstract This study introduces EDU-MAT COPERNICUS, an innovative educational platform that integrates augmented reality (AR) with satellite technologies to support mathematics and geoscience learning among primary school students. The platform features interactive mathematical tasks embedded in a narrative led by the avatar of Nicolaus Copernicus and incorporates real-world data from Earth observation systems such as Copernicus, Galileo, and European Geostationary Navigation Overlay Service (EGNOS). Designed using a user-centred approach and grounded in cognitive load theory, the prototype was evaluated through interviews with 10 mathematics tutors, user testing with 30 students, and feedback from parents. Findings suggest that AR-enhanced tasks improve students’ spatial reasoning, engagement, and motivation to learn mathematics. Teachers expressed interest in using AR tools but highlighted the need for training and integration with existing curricula. While the platform aligns with current trends in STEM (Science, Technology, Engineering, and Mathematics) education and digital pedagogy, challenges such as unequal access to technology and the small scale of testing remain. Future research should explore broader implementation and assess long-term learning outcomes. EDU-MAT Copernicus demonstrates strong potential as a scalable, interactive learning tool that combines mathematical thinking with space education in both formal and informal learning environments.